The impact of Qur’anic reading variation on clarifying the functions of Qur’anic grammar: a study of the inimitability of Qur’anic grammar. - fellah, elkhair (El Omda in Linguistics and Discourse Analysis, 2023)
The Qur'an is the starting point of the study in explaining the secrets of the miracle of Quranic grammar, and the research has been done to answer the main problem: What is the effect of heterogeneity of Quranic readings in the statement of the subtleties of grammatical miracles? To achieve the objectives of the need to employ grammar to understand the Qur'an and clarify the facts of its miracles, and the study depends on the approach of analyzing the heterogeneity of reading using the grammatical rule according to the rules of interpretation of the Qur'an, and the approach of deriving the subtleties of grammatical miracles in the Qur'an.